Predicting soil erosion in various type of land use in Rengel Village, Rengel Subdistrict, Tuban Regency - Dhina Mustikaningrum; Wella Nur Fadillah; Kristiawan; Maimunah (Universitas Pembangunan Nasional Veteran Yogyakarta, 2026)
The erosion process can lead to a decline in productivity and the soil's carrying capacity for agricultural production, as well as environmental quality. During the 2025 rainy season, Rengel became a hot topic on social media due to the flash floods that consistently occurred after heavy rains. The purpose of this study is to ascertain how different land uses contribute to erosion incidents in the Rengel subdistrict, Tuban Regency. Four land use categories were noted: rice fields, maize-chili, teak-maize agroforestry, and forests. Survey and laboratory analysis techniques were employed in this investigation. According to the calculations, the most severe erosion occurs in dryland areas. The degree of erosion risk is greatly influenced by land usage. Erosion in Rengel Village is considerably accelerated by the crop and soil conservation factors. The highest rates of erosion are found in dryland farming of 0.728 tons/ha/year. This situation is linked to a high C value, which indicates little plant cover and direct rainfall exposure of the soil's surface.